Investigation on Behaviour of Modified Bituminous Concrete Mix developed using Crumb Rubber - Gurpreet Singh, Dr. Rajiv Chauhan (International Journal of Advanced Science and Technology, 2020)
The road network in India becoming deteriorated now a days due to rapid increase in traffic and shortage of funds for the maintenance of existing roads. To minimize the construction and maintenance cost of road crumb rubber used successfully in this manner. It is also mitigating the environmental problem within the country. The Crumb rubber produced from used rubber tyre of vehicle also the native bitumen was modifying by using it. The no. of environmental issues created after disposal of this huge quantity of discarded used rubber tyre. The main reason behind this study is to develop a modified bitumen concrete mixture using scrap rubber tyre 4%, 8%,12%.16% and 20%   as partial replacement by weight of VG-10 grade bitumen. To check the suitability of modified bituminous mix in field situations Marshall Constancy test was completed and the result are examined. Laboratory investigation indicates that with the use of crumb rubber bituminous concrete mix having improved possessions than conventional mix. The modified bituminous concrete mix achieved required properties and constructed pavement present immaculate environment in economical way. The modified bitumen concrete mix with crumb rubber attaining enhanced properties than non-modified mix are suitable for road construction.